Physio-haematological and biochemical changes in dairy cows during different stages of estrus (Indian Journal of Animal Production and Management, 2018)
The present study was carried out to discriminate the prestanding, standing and end of standing heat  conditions of estrus Sahiwal cows by observing their various physiological, haematological, blood  biochemical attributes. The experiment was conducted on eight healthy, cyclic Sahiwal cows maintained  at DDD farm of ILFC, DUVASU, Mathura. Out of various physiological and hematological parameters  studied, a significant difference for three different stages of estrus in Sahiwal cows could be observed only  for rectal temperature, PCV (P
Keywords: Biochemical; Estrus; Haematological attributes; Pysiologica; Sahiwal cows